Complete genome sequence of a plant associated bacterium Bacillus amyloliquefaciens subsp. plantarum UCMB5033. Issue 3 (November 2014) - Niazi, Adnan; Manzoor, Shahid; Bejai, Sarosh; Meijer, Johan; Bongcam-Rudloff, Erik
Abstract Bacillus amyloliquefaciens subsp. plantarum UCMB5033 is of special interest for its ability to promote host plant growth through production of stimulating compounds and suppression of soil borne pathogens by synthesizing antibacterial and antifungal metabolites or priming plant defense as induced systemic resistance. The genome ofB. amyloliquefaciens UCMB5033 comprises a 4, 071, 167 bp long circular chromosome that consists of 3, 912 protein-coding genes, 86 tRNA genes and 10 rRNA operons.